PARENTS ROLE IN PROVIDING INFORMATION ABOUT ADOLESCENT REPRODUCTIVE HEALTH IN MALANG REGENCY - Lisa Purbawaning Wulandari; Tarsikah (POLTEKKES KEMENKES JAYAPURA, 2022)
Adolescence is the right time to prepare for a healthy reproductive process. Aspects that are very important for adolescents are the physical, mental, and social aspects. The role of parents is crucial in imparting knowledge to adolescents. Many teenagers are ashamed and afraid of being scolded or punished when discussing reproductive health with their parents. This research aims to examine parents' role in providing education and the reasons for not providing education about adolescent reproductive health in Malang Regency. This research method is descriptive with a cross-sectional approach. The research sample was taken through purposive sampling, obtaining 100 respondents who met the inclusion and exclusion criteria. Data was collected through a questionnaire and processed with a frequency distribution. Research findings show that less than half of the respondents have a suitable category (35.2%) in providing information about adolescent reproductive health. This offers parents a subordinate role in educating their children about adolescent reproductive health. The subordinate role is due to the lack of parental knowledge about adolescent reproductive health (68%). Education about adolescent reproductive health needs to be given to parents so that parents have the ability and can carry out their role as providers of information about adolescent reproductive health. Keywords: Adolescent reproductive health, Information provider, The role of parents